Measurement of inclusive electrons from open heavy-flavor hadron decays in p + p collisions at √s=200 GeV with the STAR detector - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physical review, 2022)
We report a new measurement of the production cross section for inclusive electrons from open heavy-flavor hadron decays as a function of transverse momentum (pT) at midrapidity (|y|<0.7) in p+p collisions at √s=200 GeV. The result is presented for 2.5<pT<10 GeV/c with an improved precision above 6 GeV/c with respect to the previous measurements, providing more constraints on perturbative QCD calculations. Moreover, this measurement also provides a high-precision reference for measurements of nuclear modification factors for inclusive electrons from open-charm and -bottom hadron decays in heavy-ion collisions.
STAR Collaboration: M.S. Abdallah, I.M. Deppner, N. Herrmann, Y. Söhngen, P.C. Weidenkaff, [und viele weitere]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 02.06.2022